The Development of Electronic Banking Services is a Requirement to Promote Financial Inclusion: Case of Algeria - نجــار , حيــاة (Finance and Business Economies Review, 2023)
This article aims to shed light on the reality of electronic banking services in Algeria and demonstrate their contribution to supporting and promoting financial inclusion. This is done by conducting an analytical study on the reality of electronic banking services in Algeria (systems of electronic payment) and showing their relationship and role in promoting financial inclusion. The results of the study concluded that despite the development of electronic banking services in Algeria and the increase in their use in recent years, their contribution to enhancing financial inclusion has not reason to the required level, especially with regard to the index of digital banking services (via the Internet and mobile phone) and the index of credit cards, which reflect the weak use of digital channels, ATMs and electronic payment terminals.